Environmental Performance and Corporate Social Responsibility (CSR) Disclosure on Company Value with Financial Performance as Mediating Variables - Muhammad Pondrinal; Ronni Andri Wijaya; Yosi Yulia; Rosi Anggraini (UPI YPTK Journal of Business and Economics, 2022)
The purpose of this study was to determine the effect of environmental performance, corporate social responsibility disclosure on firm value with financial performance as an intervening variable. The data used is secondary data in the form of financial reports (annual report) for 2015-2019. Technical analysis of the data using multiple regression analysis with random sampling with a total of 35 companies from a total population of 61 companies. The results showed that environmental performance had a positive and significant effect on firm value. Corporate social responsibility disclosure had a positive and significant effect on firm value, and financial performance had a positive and significant effect on firm value. Environmental performance has a positive and significant effect on financial performance, corporate social responsibility disclosure has no positive and significant effect on financial performance and financial performance is able to intervene in environmental performance, corporate social responsibility disclosure on company value